2008
DOI: 10.1021/ja803765r
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Transfer and Spin Dynamics in DNA Hairpin Conjugates with Perylenediimide as a Base-Pair Surrogate

Abstract: A perylenediimide chromophore (P) was incorporated into DNA hairpins as a base-pair surrogate to prevent the self-aggregation of P that is typical when it is used as the hairpin linker. The photoinduced charge-transfer and spin dynamics of these hairpins were studied using femtosecond transient absorption spectroscopy and time-resolved EPR spectroscopy (TREPR). P is a photooxidant that is sufficiently powerful to quantitatively inject holes into adjacent adenine (A) and guanine (G) nucleobases. The charge-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
137
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(154 citation statements)
references
References 104 publications
14
137
1
2
Order By: Relevance
“…[10] The synthesis of 2 s, 2 o, 3, and 4 followed that of 1. [13] Conjugates were purified by HPLC and characterized by MALDI-TOF mass spectrometry and CD (see the Supporting Information). UV/Vis spectra of reduced species were measured through 1.4 mm I.D.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] The synthesis of 2 s, 2 o, 3, and 4 followed that of 1. [13] Conjugates were purified by HPLC and characterized by MALDI-TOF mass spectrometry and CD (see the Supporting Information). UV/Vis spectra of reduced species were measured through 1.4 mm I.D.…”
Section: Methodsmentioning
confidence: 99%
“…[13,17,18] The characterization of 1-4, including mass spectrometry and circular dichroism (CD), is described in the Supporting Information.…”
mentioning
confidence: 99%
“…[6,9] More detailed studies by time-resolved methods using perylene bisimide as an internal DNA base substitution in hairpins [14] revealed that the photoexcited chromophore is able to inject electron holes into adjacent purine, but not pyrimidine bases. Electron holes that were injected primarily into adenine tracts are trapped efficiently on guanines.…”
Section: Synthesis Of the Apbi Dna Building Blockmentioning
confidence: 99%
“…[9] Additionally, two special perylene bisimide building blocks based on active esters were developed for the DNA-directed assembly of this dye in thermophilic foldamers and for single molecule measurements. [10,11] Especially, two of the mentioned perylene bisimide phosphoramidites were extensively applied to construct exceptionally stable DNA triplexes, [12,13] for electron-transfer studies, [14] for fluorescence quenching in highly sensitive molecular beacons, [15] and for forced base-flipping. [16] We showed that perylene bisimide stacks as a chiral oligochromophore inside the double helical framework.…”
Section: Introductionmentioning
confidence: 99%
“…This extremely low emission is attributable to the almost complete quenching of PDI by electron transfer from nucleobases to PDI. [17] However, when two H-H pairs were inserted between PDI and its neighboring nucleobases (H2AD/H2B), distinct emission at 550 nm was observed from PDI. As summarized in Table 1, the quantum yield (F) of H2AD/ H2B was 0.020 whereas that of D1/N was less than 0.001.…”
mentioning
confidence: 99%